Risk Factors and Current Health-Seeking Patterns of Migrants in Northeastern Mexico: Healthcare Needs for a Socially Vulnerable Population - Stoesslé, Philippe; González-Salazar, Francisco; Santos-Guzmán, Jesús; Sánchez-González, Nydia (Frontiers in Public Health, 2015)
This study identified risk factors for health and access to healthcare services of migrants during their journey across Mexico to the United States. Data were collected in shelters located in Monterrey, the largest city of northeastern Mexico, through a basic clinical examination and a survey completed by 75 migrants; 92% of them were undocumented Central Americans. During their transit, they are at a high risk of contracting, developing, and transmitting diseases. The need of working to survive affects health-seeking behavior and a constant fear of being traced keeps migrants away from public health services, which delays diagnosis and treatment of diseases. Negligent lifestyles, such as smoking, drinking (31.8% of men and 11.1% of women), and drug abuse (13% of men and 11% of women), were found. Regarding tuberculosis (TB), undocumented migrants are usually not screened, even though they come from countries with a high TB burden. Besides, they might be overexposed to TB because of their living conditions in overcrowded places with deficient hygiene, protection, and malnutrition (54.7% of the sample). Possible comorbidities like acquired immune deficiency syndrome (AIDS; 4%) and diabetes (2.7%, but probably under-diagnosed) were referred. Migrants have little TB knowledge, which is independent of their level of education or a previous experience of deportation. About one-third of the migrants were totally unfamiliar with TB-related symptoms, while 36% had correct knowledge of basic TB symptoms. We conclude that a shortage of information on the highly vulnerable migratory population combined with a lack of social support and health education among migrants may play a significant role in the spread of communicable diseases. We recommend that health authorities address this urgent, binational, public health concern in order to prevent outbreaks of emerging infections.